Diabetic Ketoacidosis Preceding Thrombocytopenia Associated Multiple Organ Failure in a Child - Patra, Kamakshya P; Scott, L Keith (JOP. Journal of the Pancreas, 2011)
Context Thrombocytopenia associated multiple organ failure is a rare but increasingly recognized condition in children. Diabetic ketoacidosis preceding thrombocytopenia associated multiple organ failure is previously unreported in pediatric patients. Case report A 12-year-old female presented with diabetic ketoacidosis along with acute pancreatitis. She further developed thrombocytopenia and renal failure over the next two days. Although hemolytic uremic syndrome/thrombotic thrombocytopenic purpura spectrum was considered, the clinical picture seemed most consistent with thrombocytopenia associated multiple organ failure. The patient was treated with serial therapeutic plasma exchanges and made a complete recovery. Conclusion A high index of suspicion of thrombocytopenia associated multiple organ failure is required in patients with diabetic ketoacidosis or pancreatitis who present with thrombocytopenia and renal failure. Plasma exchange is a life-saving intervention in such cases. Image: Diffuse enlargement and hypoattenuation of pancreas.